"It's Not About me, it's About the Community": Culturally Relevant Health Career Promotion for Indigenous Students in Australia. Issue 1 (22nd January 2009) - Kelly, Heather; Robinson, Anske; Drysdale, Marlene; Chesters, Janice; Faulkner, Susan; Ellender, Isabel; Turnbull, Leanne
Abstract: The numbers of Indigenous students studying in health career courses at the tertiary level is low. This paper describes a forum conducted as part of a project of national significance which examines the solutions and barriers for Indigenous student entry to medical and other health science education. Small group discussions and observations were used to determine how a group of Indigenous students, school age and mature, became interested in a health career, what influenced them, their expectations and where they sourced information. The initial design of the forum, based on other successful non-Indigenous health career events, was deemed inappropriate. When an Indigenous educator intervened, and used a more culturally appropriate approach, the engagement of the Indigenous students increased. The importance of culturally relevant health career promotion is a vital part of a complex series of actions needed to increase the recruitment and retention of Indigenous students into health science careers.